Fabrication and characterization of Ti–12Mo/xAl2O3 bio-inert composite for dental prosthetic applications - Yehia, Hossam. M.; El-Tantawy, Ahmed; Elkady, Omayma A.; Ghayad, Ibrahim M.; Daoush, Walid M. (Frontiers in Bioengineering and Biotechnology, 2024)
This study examines the impact of Al2O3 nanoparticles on various properties of the Ti-12Mo composite, including microstructure, density, hardness, wear rate, and electrochemical behavior. The composition of each sample was created through mechanical milling for 24 hours under an argon atmosphere. The resulting nanocomposite powders were then cold-pressed at 600 MPa and sintered at different temperatures (1350 oC, 1450 oC, and 1500 oC) for 90 minutes. Based on density measurements using the Archimedes method, the most suitable sintering temperature was found to be 1450 oC. The morphology and chemical composition of the milled and sintered composites were analyzed using back-scattering SEM and XRD. The results showed that the addition of Mo increased the Ti density from 99.11% to 99.46%, while the incorporation of 15 wt% Al2O3 in the Ti-12Mo composite decreased the density to 97.28%. Furthermore, the Vickers hardness and wear behavior of the Ti-Mo composite were enhanced with the addition of up to 5 wt% Al2O3. The sample with 5 wt% Al2O3 exhibited a Vickers hardness of 593.4 HV, compared to 320 HV for pure Ti, and demonstrated the lowest wear rate of 0.0367 mg/min, compared to 0.307 mg/min for pure Ti. Electrochemical investigations revealed that the sintered Ti-12Mo/xAl2O3 nanocomposites displayed higher corrosion resistance against a simulated artificial saliva (AS) solution compared to pure Ti. The concentrations of Ti, Mo, and Al ions released from the Ti-12Mo/xAl2O3 nanocomposites in the AS solution were within safe levels.